(untitled) (Palíndromo, 2023)
This paper presents the publications of the artist Peter Downsbrough during the 1970s, focusing on Notes on location (1972), Notes on location II (1973), Two pipes: Fourteen Locations (1974) and And (1977). It explores the connections between the paginal space, urban space, and exhibition space through a dialogue with other works created in different media throughout the artist’s journey. Books play a significant role in Downsbrough’s practice, characterized by the frequent use of minimal graphic elements combined with words and black and white photographs, reflecting on location, movement, space, and time. His works invite the audience to question and explore the relationship between visual and textual elements, offering an alternative outlook on the spaces occupied by the artworks. By exploring various contexts, Downsbrough’s works provide a distinct perspective on physical and conceptual spaces.